Policy and Regulatory Issues with Digital Businesses - Chen, Rong (World Bank, Washington, DC, 2019)
Advances in digital technology are expanding the boundaries of firms. Digital platform firms, which leverage a "platform" to create value through facilitating exchanges between two or more interdependent groups, are the new disrupters in the market. They exhibit distinct features such as scale without mass, positive network effects, accumulation of tremendous data, and a convoluted value creation process with user participation. Meanwhile, they bring more opportunities to traditional businesses by closely connecting suppliers and customers and reducing transaction frictions. Such a changing business landscape calls for adaptive policies and regulations. This policy paper lays out the key policy and regulatory issues around digital businesses. Competition laws need to be revisited to address the winner-take-all tendency of digital platform businesses. Tax systems should also be updated to close the loopholes available to digital platform businesses so that they pay their fair share to society. This paper also provides the first analysis of the World Bank's Digital Business Indicators initiative, which collects information on the existence and quality of regulations in broadband connectivity, digital payment, data privacy and security, as well as logistics, in 21 pilot countries. It aims to explore the possibilities for developing the regulatory and policy indicators that governments can work with to promote the digital economy.